Piagetian tests for the primary school - Fogelman, K. R. (Ken R.) (England National foundation for educational research, 1970)
When do children acquire basic logic to make sense of the world? This book discusses tests of logical operations, of conservation, of transitivity and seriation, of number concepts and of spatial concepts
Keywords: Concepts; Learning, Psychology of; Psychologie de l'apprentissage